Manajemen Bandwidth Queue Tree Dengan VLAN Untuk Pembelajarn Daring Di Sekolah - Hosea Adrian Pratama; Wiwin Sulistyo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The development of technology today, especially computers and the internet, makes it easier for us to get information. This has resulted in an increase in the use of computers and the internet, plus the pandemic conditions that force us to interact via the internet. Especially in a school environment, students must learn to use computers and the internet, an increase in the number of users can cause a decrease in network performance, so it must be further improved so that users are not disappointed with the decrease in quality, VLAN is a technology that allows a LAN to be divided into several different domains. And can also combine multiple networks located in the same domain. Queue tree can manage data queue and set bandwidth based on ip or port. The end result of this research is where VLANs can divide the network and manage communication between users and the queue tree can manage bandwidth